A conceptual analysis regarding the role of Indian police in combating offences against children - Dighe, Neelam and Inamdar, Shahista (Third Concept)
The Indian police play a crucial role in combating offences against children by enforcing laws, conducting investigations, and ensuring justice for victims. Their responsibilities include preventing crimes such as child abuse, trafficking, and exploitation, while also collaborating with child welfare organizations to provide support and rehabilitation. The implementation of specialized units, training programs, and awareness campaigns has strengthened their ability to address these issues effectively. However, challenges such as resource constraints and procedural delays remain, requiring continuous improvements in policies and enforcement strategies to enhance child protection. - Reproduced
Keywords: Indian police, Child protection, Crime prevention, Law enforcement, Child welfare, Trafficking, abuse, Justice system, Rehabilitation, Policy improvement